Comparative Analysis of the Content of Sum of Hydroxycinnamic Acids from Leaves of Actinidia arguta Lindl. Collected in Ukraine and China - Nadiia Kovalska; Uliana Karpiuk; Valentyna Minarchenko; Iryna Cholak; Natalia Zaimenko; Nadiia Skrypchenko; Dejiang Liu (Journal of Chemistry)
Leaves of Actinidia arguta Lindl. (A. arguta) are a promising raw material for pharmaceutical production. Actinidia is cultivated in Ukraine, and its homeland is China, so raw materials may have different origins. Hydroxycinnamic acids (HCAs) are one of the important biologically active substances of A. arguta leaves, which provide the pharmacological action of this raw material. The aim of the study was to identify and compare the quantitative content of HCAs in the leaves of A. arguta harvested in Ukraine and China in different phases of the growing season. Microscopic and phytochemical studies of the leaves of A. arguta are conducted. After histochemical reaction with the nitrite-molybdenum reagent, idioblast cells with НСАs in A. arguta leaves are stained on brick-red color. The amount of the sum of HCAs was determined by absorption UV-spectrophotometry in terms of rosmarinic acid at wavelength 505 nm after reaction with a nitrite-molybdenum reagent. It was found that the A. arguta leaves contain high levels of HCAs (to 2.69%). The highest HCAs level was recorded in July, which was decreased somewhat in August. Histochemical reactions for the detection of HCAs in fresh A. arguta leaves can be used to identify plants of the genus Actinidia Lindl., which are potential sources of HCAs. The content of HCAs is independent of the region of plant growth, but its quantity varies during the growing season. So, during July, the leaves can be collected from male plants, and during the end of August and start of September, leaves can be collected from both male and female plants. This indicates the prospect of using the leaves of A. arguta as a source of raw materials for pharmacy and medicine.